2017
DOI: 10.3390/mti1040024
|View full text |Cite
|
Sign up to set email alerts
|

The New Era of Virtual Reality Locomotion: A Systematic Literature Review of Techniques and a Proposed Typology

Abstract: Abstract:The latest technical and interaction advancements that took place in the Virtual Reality (VR) field have marked a new era, not only for VR, but also for VR locomotion. Although the latest advancements in VR locomotion have raised the interest of both researchers and users in analyzing and experiencing current VR locomotion techniques, the field of research on VR locomotion, in its new era, is still uncharted. In this work, VR locomotion is explored through a systematic literature review investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
204
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 55 publications
0
204
0
4
Order By: Relevance
“…Teleportation regained traction as a locomotion technique as part of the new wave of headsets [25]; a revival which was fueled by the provision of an arc-based point-and-teleport system in Steam's (free) VR plugin for Unity and Unreal. First-person games will typically offer teleportation as a default locomotion technique for novice VR users and continuous free motion for the more experienced.…”
Section: Teleportationmentioning
confidence: 99%
“…Teleportation regained traction as a locomotion technique as part of the new wave of headsets [25]; a revival which was fueled by the provision of an arc-based point-and-teleport system in Steam's (free) VR plugin for Unity and Unreal. First-person games will typically offer teleportation as a default locomotion technique for novice VR users and continuous free motion for the more experienced.…”
Section: Teleportationmentioning
confidence: 99%
“…It was shown that VE has an influence on emotional states and stress resistance [3]; thus, this one could activate the corresponding behavior like in the real world [4]. The analysis mentioned above shows the potential of VR in the context of increasing the effectiveness of learning and simulation training.…”
Section: Introductionmentioning
confidence: 95%
“…The purpose of our model is to make a better Virtual Reality Experience bringing new elements that has not been introduced in mobile virtual reality [1]. Generation 3D virtual experience from a single 2D image through a computer generated system is highly unlikely, due to the lack of depth information and dimensional limitations [2].…”
Section: Motivations and Goalsmentioning
confidence: 99%
“…Rollmann 1st introduced the idea of 3D anaglyph through viewing a yellow blue drawing with red and blue glasses [5]. He also found that with a red and blue drawing the outcome was not as perfect as it is with the yellow and blue drawing because the red and blue line drawing are not visible with the yellow and blue glasses [1,6]. In 1858, Joseph D'Almeida projected the 1st 3D magic lantern where the audience wore green and red Google to view the 3D lantern [1/6].…”
Section: Literature Reviewmentioning
confidence: 99%